2006
DOI: 10.1103/physrevb.74.235104
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and transverse diffusion of conduction-electron spins on stacks of fluoranthene radical cations

Abstract: The temperature dependence and anisotropy of the conduction-electron spin diffusion coefficient D͑T͒ of three single crystals of the organic conductor ͑fluoranthene͒ 2 PF 6 with defect content varying between 7 ϫ 10 −5 and 1% per formula unit have been determined. D ʈ / D Ќ varies between 2 ϫ 10 4 and 100 in the metallic phase. The defect dependences of the Peierls transition, microwave conductivity, magnetic susceptibility, and transverse relaxation rate are presented as well and their relations are discussed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“… T 1 map derived from a slice in a (FA) 2 PF 6 single crystal. Pixel volume ( X × Y × Z ) is (100 × 30 × 45) m̈m 3 . The graphs represent detailed T 1 values fitted for the indicated regions of the image 21 …”
Section: Results For Organic Conductorsmentioning
confidence: 99%
See 4 more Smart Citations
“… T 1 map derived from a slice in a (FA) 2 PF 6 single crystal. Pixel volume ( X × Y × Z ) is (100 × 30 × 45) m̈m 3 . The graphs represent detailed T 1 values fitted for the indicated regions of the image 21 …”
Section: Results For Organic Conductorsmentioning
confidence: 99%
“…It is thus concluded that the systematic variation of the defect content in the different growth sectors is of relevance in spite of its low absolute value (10—1000 ppm per formula unit range). The diffusion coefficient parallel to the stacking axis is reduced for increasing defect content, whereas the perpendicular component increases, but to a much smaller extent 3 . In most simple non‐magnetic metals, defect spins relax faster to the lattice than conduction electron spins, thus their mutual exchange interaction is in favor of the total conduction electron spin‐lattice relaxation.…”
Section: Results For Organic Conductorsmentioning
confidence: 99%
See 3 more Smart Citations